Prevalence of Liver Injury in 445 Patients with Corona Virus Disease-19 - Muhammad Aasim Khan, Hafeez Ud Din, Kapeel Raja, Naeem Abbas Gilani, Mohammad Hanif, Tariq Hassan (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Severe acute respiratory syndrome COVID-19 disease patients are susceptible to abnormal liver function and its prevalence varies from 16 to 52%. The present study aimed to assess the incidence of liver injuries in 445 patients with COVID-19 infections. Methodology: This retrospective study was carried out on 445 COVID-19 infected patients in the department of Gastroenterology, Northwest General Hospital & Research Centre Hayatabad Peshawar and Bacha Khan Medical Complex, Swabi for the duration of six-months from February 2021 to July, 2021. The patient’s demographic details, COVID symptoms, laboratory tests, and previous illness history were recorded. COVID-19 was diagnosed through Reverse transcriptase-polymerase chain reaction (RT- PCR) via oropharyngeal and nasopharyngeal swabs. Ethical approval was taken from the institutional ethical committee. SPSS version 21 was used for data analysis. Results: Of the total 445 COVID-19 infected patients, the incidence of elevated, mild elevated, moderately elevated, and severely elevated Aspartate transaminase (AST) was 208 (46.8%), 47 (10.6%), 10 (2.3%), and 4 (0.9%) respectively. The prevalence of symptomatic abnormal liver was 89% compared to asymptomatic 81% at p=0.001). Moderate, mild, and elevated Alanine transaminase (ALT) was 1.2%, 10.9%, and 29.8% respectively. The incidence of respiratory symptoms and loose stool was 44.2% and 12.3% compared to 30.3% and 3.8% respectively. Abnormal liver patients were more susceptible to severe COVID-19 disease 26.7% compared to 14.2%. Conclusion: Our study found that patients with COVID-19 had a high rate of liver test abnormalities. The majority of the patients had transaminase elevations that were borderline or mild. Abnormal liver disease patients are more susceptible to symptomatic disease, mortality, and severe COVID-19 disease.